Optimization of heat transfer in heat pipes using nanofluids at various inclinations and filling levels - Prabhu Alphonse; Karthikeyan Muthukumarasamy; Sivakumar Elumalai; Manikandan Kadamban; Ratchagaraja Dhairiyasamy (Case Studies in Thermal Engineering)
This study investigates the thermal performance of heat pipes filled with various nanofluids under different operational conditions, including inclination angles, filling ratios, and heat inputs. The objective was to evaluate the impact of silver (Ag), aluminum oxide (Al₂O₃), and multi-walled carbon nanotube (MWCNT) nanofluids on thermal resistance and heat transfer coefficients. Experiments were conducted using a heat pipe with a 750 mm length divided into evaporator, adiabatic, and condenser sections. Nanofluids were tested at filling ratios of 60 %, 70 %, 80 %, and 90 %, and inclination angles of 0°, 45°, 60°, and 90°. The results show that MWCNT nanofluid exhibits the lowest thermal resistance, decreasing from 1.23 K/W at 0° to 0.61 K/W at 90°, outperforming other fluids. The overall heat transfer coefficient of MWCNT increased to 4900 W/m2K at a 90 % filling ratio and 90° inclination. The study concludes that MWCNT nanofluids provide the highest thermal efficiency, particularly at steeper inclinations and higher filling ratios, making them ideal for high-performance thermal management applications.